Early work-environmental indicators of bullying in an academic setting: a longitudinal study of staff in a medical university. Issue 12 (2nd December 2021) - Björklund, Christina; Vaez, Marjan; Jensen, Irene
ABSTRACT: The purpose of this study was to use a longitudinal approach to investigate the association between work-related psychosocial factors and workplace bullying in an academic setting. A questionnaire was sent out three times to about 4500 academic- and non-academic staff in a medical university. Those two group were analyzed together and separately. Logistic regression analyses were used to calculate odds ratios (OR). In the study, we found that factors such as lack of support, low control, inconsistent role demands, poor leadership, poor organizational climate, high sickness absence and high sickness presence can be important predictors of future bullying. We found that factors in an academic setting differ somewhat for academics and non-academic staff. This might indicate that type of job should be take into consideration in attempts to successfully prevent bullying at an early stage.